Kappa-carrageenan as immunostimulant to control infectious myonecrosis (IMN) disease in white shrimp Litopenaeus vannamei - Febriani, Dian; Sukenda, .; Nuryati, Sri (Jurnal Akuakultur Indonesia, 2013)
ABSTRACT This study evaluated the modulation of non-specific immune response, growth, and disease resistance of white shrimp,  Litopenaeus vannamei against infectious myonecrosis virus (IMNV). The first stage of this study evaluated the different dose of k-carrageenan administration i.e. 5, 10, and 15 g/kg feed for four weeks of rearing period, while the later studied evaluated about the frequency of administration i.e. daily, seven days interval, and 14-days interval for five weeks of rearing period. Both stages had positive and negative control and performed in complete randomized design. The parameters of observation consisted of immune parameters, clinical symptoms, growth, and survival. Shrimp were fed three times a day at feeding rate of 4–5% of body weight/day. IMNV Challenge test was performed by feeding the shrimp via oral route at a level 10% of body weight for three consecutive days, followed by 14-days observation. The results showed that shrimp administered with k-carrageenan at a concentration of 15 g/kg feed showed the best performance of all concentration tested. The shrimp’s haemocyte count, phagocytes activity, phenoloxidase activity, and relative growth were 12±0.72×106 cell/mL; 34.67±0.58%; 0.511±0.10; and 86.15% respectively. After challenged, the survival was 85±7.07%. Moreover, application in 14 days at 7-days interval gave 88.57% relative growth and 93±5,8% survival, which were higher than other treatments. The administration of k-carrageenan at concentration of 15 g/kg with 14 days interval on white shrimp juveniles showed higher immunostimulatory effect and better protection against IMNV. Keywords: kappa-carrageenan, immunostimulant, IMNV, Litopenaeus vannamei  ABSTRAK Penelitian ini mempelajari pemberian kappa-karagenan dalam memodulasi respons imun nonspesifik, pertumbuhan, dan resistensi udang vaname Litopenaeus vannamei terhadap infeksi infectious myonecrosis virus (IMNV). Tahap pertama mengetahui dosis pemberian k-karagenan sebesar 5, 10, dan 15 g/kg pakan selama empat minggu pemeliharaan, sedangkan tahap kedua mengevaluasi frekuensi pemberian k-karagenan, yaitu setiap hari, tujuh hari, dan 14 hari secara berulang dengan interval tujuh hari selama lima minggu pemeliharaan. Kedua tahap penelitian menggunakan kontrol positif dan negatif dalam rancangan acak lengkap. Parameter pengamatan terdiri atas respons imun, gejala klinis, pertumbuhan dan kelangsungan hidup udang vaname. Udang diberi makan tiga kali sehari dengan FR 4–5% biomassa/hari. Infeksi IMNV dilakukan secara oral sebesar 10% biomassa selama tiga hari berturut-turut, dan diamati selama 14 hari. Hasil penelitian menunjukkan bahwa udang yang diberikan k-karagenan 15 g/kg pakan memperoleh hasil terbaik. Total hemosit, aktivitas fagositosis, aktivitas phenoloxidase, dan pertumbuhan relatif udang masing-masing adalah 12±0,72×106 sel/mL; 34,67±0,58%; 0,511±0,10 dan 86,15%, dengan kelangsungan hidup udang setelah diinfeksi IMNV sebesar 85±7,07%. Frekuensi pemberian 14 hari secara berulang dengan interval tujuh hari memberikan hasil kelangsungan hidup terbaik sebesar 88,57% dan pertumbuhan relatif sebesar 93±5,8%. Kesimpulan dari penelitian ini bahwa, pemberian k-karagenan 15 g/kg dan interval 14 hari menunjukkan respons imun dan perlindungan yang lebih baik terhadap IMNV. Kata kunci: kappa-karagenan, imunostimulan, IMNV, Litopenaeus vannamei